Reporting of measures of accuracy in systematic reviews of diagnostic literature - Khan Khalid S; Honest Honest (BMC, 2002)
Abstract Background There are a variety of ways in which accuracy of clinical tests can be summarised in systematic reviews. Variation in reporting of summary measures has only been assessed in a small survey restricted to meta-analyses of screening studies found in a single database. Therefore, we performed this study to assess the measures of accuracy used for reporting results of primary studies as well as their meta-analysis in systematic reviews of test accuracy studies. Methods Relevant reviews on test accuracy were selected from the Database of Abstracts of Reviews of Effectiveness (1994-2000), which electronically searches seven bibliographic databases and manually searches key resources. The structured abstracts of these reviews were screened and information on accuracy measures was extracted from the full texts of 90 relevant reviews, 60 of which used meta-analysis. Results Sensitivity or specificity was used for reporting the results of primary studies in 65/90 (72%) reviews, predictive values in 26/90 (28%), and likelihood ratios in 20/90 (22%). For meta-analysis, pooled sensitivity or specificity was used in 35/60 (58%) reviews, pooled predictive values in 11/60 (18%), pooled likelihood ratios in 13/60 (22%), and pooled diagnostic odds ratio in 5/60 (8%). Summary ROC was used in 44/60 (73%) of the meta-analyses. There were no significant differences in measures of test accuracy among reviews published earlier (1994-97) and those published later (1998-2000). Conclusions There is considerable variation in ways of reporting and summarising results of test accuracy studies in systematic reviews. There is a need for consensus about the best ways of reporting results of test accuracy studies in reviews.